Konsep dan Prinsip Pendidikan Kristiani Menurut Ignatius Loyola - Devi Lestary; Grasela Sinta2; Sarmauli Sarmauli (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
This research addresses the growing tendency of contemporary education to prioritize cognitive achievement while marginalizing character formation and spiritual development, resulting in an imbalanced educational paradigm that affects the holistic growth of learners in various educational contexts. In response, the research critically examines the concept and principles of Christian education as articulated by Ignatius Loyola, particularly in relation to contemporary educational challenges and the need for meaningful transformation in learning processes today. The study employs a qualitative approach using a literature review method, drawing on relevant academic sources such as books, peer-reviewed journal articles, and theological writings to support systematic and critical analysis. The findings indicate that Ignatian educational thought emphasizes holistic human formation through the integration of intellectual, moral, and spiritual dimensions, grounded in the principles of Ad Majorem Dei Gloriam, Cura Personalis, and Find God in All Things, which together foster reflective, value-oriented learning. The study contributes to contemporary educational discourse by offering an alternative framework that promotes holistic development, strengthens character formation, and addresses the limitations of cognitively oriented educational models in diverse educational practices.